The Feminist Discourse in the Blanca de los Ríos’ Journalistic Work - Escabias Toro, Juana (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The purpose of this article is to analyze from a feminist perspective the journalistic discourse of Blanca de los Ríos, Spanish writer and journalist born in 1859. Her activity to fight discrimination against women was constant in her life. Despite this, she does not figure in the history of Spanish feminism. Our approach analyzes her discourse by combining the methodology of critical analysis focused on the conception of ideology and hegemony with a transversal gender approach, also highlighting her biographical trajectory. The results found that her discourse is fully valid in relation to what is established by current gender studies, in concepts such as stereotypes, biases, mandates or gender gap or recognition of difference. As a contribution we apply these notions in detail to her journalistic articles, concluding that she deserves a rediscovery that allows her to be included in the history of Spanish Feminism.